Analysis of students self-efficacy level - Cindy Asli Pravesti; Elia Firda Mufidah; Eva Nanda Nurlitasani; Maghfirotul Lathifah; Peppy Sisca Dwi Wulansari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to assess the level of self-efficacy among students at SMPN 9 Blitar. This study uses a self-efficacy measurement scale developed by the researcher. The research sample, consisting of 79 students, was selected through purposive random sampling. The data analysis method used descriptive statistics using SPSS. The scale used in this study is the self-efficacy scale. The results indicated that 75 students were in the high self-efficacy category, while 4 students were in the moderate self-efficacy category. These findings can assist counselors in designing effective guidance and counseling programs to help students at SMPN 9 Blitar achieve their developmental tasks optimally.